Efeitos da imersão em água fria na recuperação pós-exercício: análise conjunta de parâmetros clínicos, funcionais, metabólico e autonômico - Micheletti, Jéssica Kirsch [UNESP] (2015)
Cold water immersion (CWI) appears in the current scenario as an effective recuperative technique in sports, working on different outcomes. However, the concept of post-exercise recovery deserves attention, since analysis of individual parameters seem to hurt this concept. Therefore, the construction of a drawing from a unique mechanism of stress, with the same technique application feature and involving elements of various dimensions seems pertinent. Objective: To analyze the immediately recovery after a training and to verify the isolated and combined behavior of clinical, functional, metabolic and autonomic parameters from the use of immersion in cold water as recuperative technique. Methods: A sample of 64 football players, randomized into two groups, control group (CG) and experimental group (EG). The procedures were performed in two stages. 1st: Participants underwent basic tests of muscle function. 2nd: After a week of rest, underwent a key workout (50 minutes) and immediately after the intervention performed for 15 minutes, GE received the IAF (13 ± 1 ° C) and GC stay sitting. The investigated variables were subjective perception of pain, perceived recovery, abnormal sensitivity, blood lactate concentration, cardiac autonomic modulation and functional tests, these were measured during specific recovery times up to a maximum two hours post training. Statistical analysis was performed using the statistical package SPSS Statistics 22.0. For numeric data, the functional markers, the distribution of the data was tested (Komolgorov-Smirnov) and as normal we used the t student test for independent samples. For the other markers were tested sphericity data (Mauchly test). Data were analyzed using analysis of variance for repeated measures (Bonferroni post-test). For dichotomized data was performed for data on frequency (%) of total score (all outcomes) Mann-Whitney test. And the absolute frequency (cases) chi-square test. To calculate the probability of recovery was used logistic regression. Results: numerical data: For clinical outcomes, statistically significant differences were observed between the groups, and both recover at the same time (15 minutes post training). For metabolic outcomes, both groups recovered at the same time (2 hours after exercise). The function outcome, there were no significant differences between moments and between groups. For the analysis of heart rate variability was observed anticipation of recovery of all indices in the EG compared to the CG. Dichotomized data: Analysis together variable categories did not show better efficacy CWI technique where the GC has recovered 63.4% and GE: 69,17. When assessed isolated systems there is a better chance of technique likely to be better for metabolic and autonomic outcomes. Conclusions: General: When analyzed together the categories of outcomes, the techniques presented close recoveries, with no statistical differences. Specific: When analyzed the categories of isolated outcomes there is high probability of recovery within 2 after training hours for participants of the two groups in clinical, metabolic, autonomic and functional, except for the outcome of maximal voluntary isometric contraction (in the analysis of dichotomized data). For groups of metabolic and autonomic variables the probability of recovery was higher for the GE (in the analysis of dichotomized data). Finally, the autonomic system is benefit from the technique in both analyses.